2023
DOI: 10.3390/magnetochemistry9090211
|View full text |Cite
|
Sign up to set email alerts
|

Surface Modifications of Superparamagnetic Iron Oxide Nanoparticles with Polyvinyl Alcohol and Activated Charcoal as Methylene Blue Adsorbents

Linh Doan

Abstract: As novel methylene blue adsorbents, polyvinyl alcohol and activated charcoal were used to modify the surface of superparamagnetic iron oxide nanoparticles. The adsorption capacity after 69 h was 26.50 ± 0.99–40.21 ± 1.30 mg/g, depending on the temperature (333.15, 310.15, and 298.15 K) and the initial concentration of methylene blue, which was between 0.017 and 0.020 mg/mL. Based on thermodynamics parameters, the adsorption process can be considered to be spontaneous endothermic physisorption. Kinetics studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 126 publications
1
7
0
Order By: Relevance
“…To determine the classification of IONPs in the samples, XRD was used to determine the crystal structure as well as the crystallite size of the materials. According to the results shown in Figure 3, the peaks appeared at 2θ positions of 30.22°, 35.58°, 43.22°, 53.68°, 57.27°, and 62.85°, which are denoted as being correlated with the magnetite (based on the corresponding hkl indices), similar to previous publications [6,17,31]. It can be concluded that the IONPs presented in the materials were SPION, and the mixture of materials with SPION can be proved to be a successful blend according to the similar peaks shown in the diffractograms.…”
Section: Xrd Analysissupporting
confidence: 88%
See 4 more Smart Citations
“…To determine the classification of IONPs in the samples, XRD was used to determine the crystal structure as well as the crystallite size of the materials. According to the results shown in Figure 3, the peaks appeared at 2θ positions of 30.22°, 35.58°, 43.22°, 53.68°, 57.27°, and 62.85°, which are denoted as being correlated with the magnetite (based on the corresponding hkl indices), similar to previous publications [6,17,31]. It can be concluded that the IONPs presented in the materials were SPION, and the mixture of materials with SPION can be proved to be a successful blend according to the similar peaks shown in the diffractograms.…”
Section: Xrd Analysissupporting
confidence: 88%
“…Similar to previous publications, using UV-VIS spectroscopy, Q t , %LC, and %EE were evaluated, as shown in Table 3 [6,17,31]. As shown in Table 3 and Figure 7a, the adsorption capacity of SPION/PVA/CS/AC after 310 h was 7.6 ± 0.2 mg/g, 14.9 ± 0.1 mg/g, and 22.4 ± 0.05 mg/g at MB concentrations of 0.015 mg/mL, 0.02 mg/mL, and 0.025 mg/mL, respectively.…”
Section: Adsorptionmentioning
confidence: 90%
See 3 more Smart Citations